Detection of haemodynamic obstruction in hypertrophic cardiomyopathy using the sub-aortic complex: a cardiac MRI and Doppler study. Issue 6 (June 2023) - Chen, Z.; Cui, C.; Yin, G.; Jiang, Y.; Wu, W.; Lei, J.; Guo, S.; Zhang, Z.; Zhao, S.; Lu, M.
Abstract : AIM: To investigate the "sub-aortic complex (SAC)", a new cardiac magnetic resonance imaging (CMRI)-derived parameter, for the evaluation of left ventricular (LV) outflow tract (LVOT) obstruction in patients with hypertrophic cardiomyopathy (HCM), compared with conventional CMRI parameters and Doppler echocardiography. MATERIALS AND METHODS: A total of 157 consecutive patients with HCM were recruited retrospectively. The patients were divided into two groups, 87 with LVOT obstruction and 70 without obstruction. The SAC was defined as a specific anatomical SAC affecting the LVOT, which were measured on the LV three-chamber steady-state free precession (SSFP) cine image at the end-systolic phase. The relations between the existence and severity of obstruction and SAC index (SACi) were evaluated using Pearson's correlation coefficient, receiver operating characteristic (ROC) curves, and logistic regression. RESULTS: The SACs were significantly different between the obstructive and non-obstructive groups. The ROC curves indicated that the SACi was able to discriminate obstructive and non-obstructive patients with the best predictive accuracy (AUC = 0.949, p< 0.001). The SACi was an independent predictor of LVOT obstruction and there was a significant negative correlation between resting LVOT pressure gradient and SACi ( r= 0.72 p< 0.001). In the subgroup of patients with or without severe basal septal hypertrophy, the SACi was still able to predict LVOT obstruction with excellent diagnostic accuracy (AUC = 0.944 and 0.948, p< 0.001, respectively). CONCLUSION: The SAC is a reliable and straightforward CMRI marker for assessing LVOT obstruction. It is more effective than CMRI two-dimensional flow in diagnosing the severity of obstruction in patients with HCM. Highlights: SAC is a reliable and straightforward CMR marker for assessing LVOT obstruction. SAC evaluated the severity of LVOT obstruction is more effective than CMR 2D flow. SAC can predict LVOT obstruction in HCM without severe basal septal hypertrophy.